A computational investigation to analyze the effects of different rotor parameters on hybrid hydrokinetic turbine performance. (1st March 2020) - Saini, Gaurav; Saini, R.P.
Abstract: Cross flow hydrokinetic turbines have been considered a decent choice for riverine applications. Under the present work, performance of hybrid rotor cross flow hydrokinetic has been investigated for different rotor parameters. The proposed hybrid rotor is the combination of two conventional turbine rotors (Savonius and Darrieus). Investigations have been performed by considering flow velocity varying in the range from 0.5 m/s to 2.0 m/s. The performance of hybrid rotor was assessed in term of power coefficient ( C P ) and torque coefficient ( C T ). Further, comparison of hybrid rotor and single Darrieus rotor has been carried out on the basis of their performance. Flow behaviour across the turbine vicinity is analyzed and discussed with the pressure, velocity contours and velocity streamlines. It has been found that radius ratio and attachment angle play a crucial role in performance enhancement with reduction in torque fluctuations. For the considered range of rotor parameters, the maximum power coefficient ( C Pmax ) and average torque coefficient ( C Tavg ) were obtained as 0.109 and 0.1276 corresponding to radius ratio of 0.6 at an attachment angle of 90°. Further, power coefficient and torque coefficient of hybrid rotor are found to be improved by 37.97% and 35.88% respectively as compared to single Darrieus rotor. Highlights: Flow distributions were discussed across the hybrid turbine rotor. Numerical simulations were performed for flow velocity range of 0.5 m/s-2.0 m/s. Coefficient of power ( C P ) is considered as the assessment parameter for turbine. Effects of radius ratio and attachment angle are numerically investigated. C Pmax is found as 0.109 at 0.6 radius ratio and 90° attachment angle.